Batch Adsorptive Removal Studies of Chromium(VI) using Cellulose-based Crosslinked Hydrogel - Periyannan, Govindaswamy; Latha, Srinivasan (Asian Journal of Chemistry, 2025)
This study reports the removal of hexavalent chromium [Cr(VI)] using a novel cellulose-based crosslinked hydrogel synthesized from chitosan oligosaccharide (COS), nanocrystalline cellulose (NCC), acrylamide (AM) and N.N′-methyl bis-acrylamide (MBA) as crosslinker. The hydrogel was characterized by FTIR, XRD, SEM, EDAX, particle size analysis and zeta potential. Batch adsorption experiments evaluated the effects of pH, contact time, initial Cr(VI) concentration and adsorbent dosage. Results showed that the COS-NCC-g-AM/MBA hydrogel exhibited high adsorption capacity and removal efficiency under optimal conditions. The adsorption was strongly influenced by operational parameters. Overall, the composite presents a sustainable, low-cost and efficient solution for removal of Cr(VI) from wastewater, demonstrating significant potential for water purification and environmental remediation applications.